From Hashtag to Policy: The Power of Digital Activism in Transforming Global Narratives - Susie Sugiarti; Zaldy Handi Aditia; Andi Banus Achir; Maya May Syarah (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
This study explores how digital activism, driven by social media campaigns, can shape global narratives and influence policy transformation. Adopting a qualitative case study approach, the research examines major digital movements such as #BlackLivesMatter and #FridaysForFuture. Through thematic analysis, it identifies how narrative construction, collective awareness, and political support interact to generate tangible policy outcomes. The findings highlight that effective digital advocacy requires more than viral messaging it depends on emotional resonance, sustained engagement, and the presence of institutional receptiveness. The study contributes to digital political communication theory by integrating framing strategies, participatory mobilization, and governance responsiveness. Practically, it offers insights for activists and policymakers to align digital strategies with policy making structures in order to foster democratic reform.